(3cJGH ehGRjf GdGMLGQ Ydi QCi HdjfGSs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3SHMGf GdeHOC GdeYjO GdaYGd deG jQjO hbO JbOe dPG bHd cJGHfG gPG cJGHGf ai eYQaI ehGRjf GdGMLGQ hfMf PGcQhf ai cJGHfG gPG UhQI GNdGW GdCMLGQ hGdCTLGQ hGdMjhGf s
(3BNQgG (B:s
(3hGYde Cfc eJi NGdaJ TjFkG eeG PcQfGg de jJe Yedc Yed eKGd Pdc Cf dh bGd aGYed JQjO WHN bOQ ai GdbOhQ GdeTghQI Je GdLRA GdKGdK ef cJGH GdGMLGQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdK YTQs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9318) s
Keywords: (3GdadSaI hGdefWbs